FROM THREAT TO OPPORTUNITY: THE CASE OF BAM, IRAN - Mokhtari Taleghani, Eskandar; Vatandoust, Rasool; Amirjamshidi, Glavije (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The earthquake of December 2003 in Bam should be considered the worst hazard to befall one of the oldest standing earthen structures of the world. The disaster sever ely affected its historical and cultural landscape and de stroyed a signiicant amount of national heritage. This heritage was comprised of religious, residential and public buildings, as well as the ancient city of Bam. The tragedy not only ruined the character of the buildings from their core, but also made earthen resources a distrusted category of building materials in people’s minds. Subsequently, the culture of building with earthen architecture lost its good traditional reputation with the risk of tragedy in an earthquake. Six years of hard work after the earthquake, which began with the creation of the Recovery Project of Bam’s Cultural Heritage (RPBCH), along with the help of other national and international partners, made it possible for conservators, engineers and architects to rebuild the lost trust in the public mind. In the aftermath of the earthquake, some major opportunities for meaningful progress in conservation presented themselves. The development of new guidelines for crisis management in cultural heritage, valuable identiication of Bam’s heritage, recognition of different aspects of the existing earthen architecture, assessment of new technology for conserving earthen monuments and learning the techniques to use them in other historic earthen heritage were among the results of capitalization of these opportunities. In addition to these achievements, educating and training the elderly craftsmen, and the combination of scientiic methods with traditional methods also helped to gain the trust of residents. This paper reviews these activities and presents the results within a research framework; it identiies good practices in using the opportunities and proposes new ideas to tackle potential future challenges.